Synthesis challenges for graphene industry - Lin, Li; Peng, Hailin; Liu, Zhongfan (Nature materials, 2019)
The past few years have witnessed significant development in graphene research, yet a number of challenges remain for its commercialization and industrialization. This Comment discusses relevant issues for industrial-scale graphene synthesis, one of the critical aspects for the future graphene industry.